Microcontroller based oscilloscope - Tan, Wee Pin (2015)
The objective of this report is to document the project ‘Small signal, low cost virtual oscilloscope’. In the older days, an oscilloscope was called an oscillograph and in recent years, cathode-ray oscilloscope and digital storage oscilloscope were invented. A typical oscilloscope is equipped with basic functions like measuring the voltages, frequency and displaying of waveforms. The virtual oscilloscope contains basic functions like variable divisions across the axes, pausing the display and control of triggering. The voltage range of the signal that can be displayed varies from 800ɥV to 3.3V (governed by the microcontroller’s supported voltage range) and can be increased by changing the microcontroller. Bluetooth transmission will be used to transmit the digitalized signal processed by Arm microcontroller to an iPAD application (of another FYP).